Existência de solucões periódicas em equações diferenciais funcionais do tipo retardado - Vendramini, Elisa Zanuncio (1977)
In recent years, there have been many papers devoted to the existence of periodic solutions of both autonomous and non-autonomous functional differential equations. It would require a monograph to bring together some of these results. One of the purposes of this monograph is to use two particular types of new fixed point theorems, one due to Brower an other due to Browder, to obtain the existence of periodic solutions of functional differential equations of retarded type.